People with disabilities in the labor market facing the challenges of the contemporary world - Całek, Grzegorz; Niedbalski, Jakub; Racław, Mariola; Sałkowska, Marta; Sztobryn-Giercuszkiewicz, Joanna; Żuchowska-Skiba, Dorota; Agnieszka Gralak (Niepełnosprawność i praca: Wymiary, konteksty, perspektywy, 2024)
Chapter ten serves as an introduction to the monograph, which focuses on topics related to disability in work contexts. The individual parts of the monograph analyze the situation of people with disabilities in the labor market, discussing the problems and barriers they face when seeking employment and performing professional duties, and presenting ways to address them. It also focuses on issues related to supporting people with disabilities and those at risk of losing their ability to work.The various perspectives presented in the monograph aim to highlight the problems, existing or proposed solutions, and changes occurring in the labor market. In the context of these challenges and perspectives, both for people with disabilities and for employers and those responsible for education and vocational activation programs, the monograph seeks to present a comprehensive picture of the situation. It should be noted that despite the increase in employment in Poland, there are still barriers hindering the full participation of people with disabilities in the labor market. These barriers have both systemic and social roots, requiring a holistic approach and interdisciplinary analysis of existing problems.